Defamation suit : Internet Service Provider (ISP) at risk! / Norazlina Abdul Aziz and Irini Ibrahim - Abdul Aziz, Norazlina; Ibrahim, Irini (Universiti Teknologi MARA, Shah Alam, 2012)
World has become smaller, communication and transportation have been expedite, discharging bills and payment have become much easier with the assistance of an impressive technology. Unfortunately, as many have enjoyed advantage of the new technology, there are more of them who have misused the technology. The nature of convergence technology requires a new regulatory framework to guide future development. Policing a global operation like the Internet involves policing citizens from countries with widely differing domestic laws, cultures and social mores. An overwhelming usage of the Internet has contributed to uncontrollable activities which exposed harms to once private life and one of it is dissemination of defamatory words. This study will critically examine the adequacy of the Malaysian legal framework in governing the rights and liabilities of the internet service provider i.e The Multimedia and Telecommunication Act 1998 and The Defamation Act 1957. The objectives underlying this study is to examine the Malaysian legal standing on the rights and liabilities of the Internet Service Provider in Malaysia under the defamation claims and looking into the approach taken by the advanced jurisdiction of United Kingdom and European Union into solving the inadequacy of the said laws with the intention of recommending the most relevant amendment to the existing Malaysian legal framework on the liabilities and protection for the ISP under a Defamation claim.